On the forgotten topological index of signed graphs - Pirzada, Shariefuddin; Rashid, Mir Riyaz Ul (Ukrains’kyi Matematychnyi Zhurnal, 2026)
UDC 519.17 The forgotten topological index denoted by F(G) of a graph G=(V,E) is defined as follows: F(G)=olimits_i=1^n\!d_v^3, where d_v denotes the degree of the vertex v. We extend the notion of forgotten topological index to signed graphs and introduce the MS-index of a signed graph. Moreover, we determine the forgotten topological index for the tensor product, Cartesian product, lexicographic product, strong product, symmetric difference, and the joint of the graphs G_1 and G_2 in terms of the forgotten topological index, the first Zagreb index, and the M-1ptS-index of signed graphs Σ_1=(G_1,σ_1) and Σ_2=(G_2,σ_2), along with their sizes and orders.